2019
DOI: 10.1002/mgg3.834
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequence analysis in consanguineous Pakistani families inheriting Bardet‐Biedle syndrome determined founder effect of mutation c.299delC (p.Ser100Leufs*24) in BBS9 gene

Abstract: Background Bardet‐Biedl syndrome (BBS) is characterized by a heterogeneous phenotypic spectrum of retinopathy, intellectual disability (ID), obesity, polydactyly, and kidney dysfunctions as the major clinical features. Genetic investigations have reported 21 BBS genes, the products of which are mostly located at the centrosome, basal body or the ciliary transition zone. Methods In the present genetic report, we analyzed two apparently unrelated consanguineous BBS families from Dera Ismail Khan (D.I.Khan) distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The patients' parents are nonconsanguineous, but the mutation analysis indicated that this family might be inbred. In previous reports, the founder effect of mutation c.299delC (p.Ser100Leufs * 24) in the BBS9 gene was observed in consanguineous Pakistani families [15,16].…”
Section: Discussionmentioning
confidence: 90%
“…The patients' parents are nonconsanguineous, but the mutation analysis indicated that this family might be inbred. In previous reports, the founder effect of mutation c.299delC (p.Ser100Leufs * 24) in the BBS9 gene was observed in consanguineous Pakistani families [15,16].…”
Section: Discussionmentioning
confidence: 90%
“…Previously, three different mutations in the BBS3 gene have been identified in three Pakistani families affected with BBS; one of the homozygous variants is a deletion of 54 Kb [31,40,41]. Notably, four other large deletions in BBS3 were found in BBS families from Saudi Arabia, France and USA [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…BBS is a ciliopathy disorder that involves various body systems and mostly follows an autosomal recessive inheritance pattern; however, triallelic inheritance is also reported as a possible mechanism by some studies [ 18 20 ]. There are 21 genes that are associated with BBS so far; among those, BBS1 and BBS10 are mostly reported from North America and Europe, respectively, whereas BBS2 , BBS4 , BBS5 , and BBS12 are more prevalent in the Middle East and North Africa [ 11 , 21 , 22 ]. Based on previous and our current study, only eight BBS mutated genes ( BBS1 (OMIM #209901) [ 23 ], BBS2 (OMIM #606151), BBS3 / ARL6 (OMIM #608845), BBS5 (OMIM #603650) [ 24 ], BBS8 / TTC8 (OMIM #608132) [ 25 , 26 ], BBS9 (OMIM #615986) [ 9 , 27 ], BBS10 (OMIM #610148) [ 28 30 ], and BBS12 (OMIM #610683)) [ 31 ] have been reported in the Pakistani population.…”
Section: Discussionmentioning
confidence: 99%